2012
DOI: 10.1371/journal.pone.0029977
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Declines More in Tenofovir- than Abacavir-Based Antiretroviral Therapy in Low-Body Weight Treatment-Naïve Patients with HIV Infection

Abstract: ObjectiveTo compare the rate of decline of renal function in tenofovir- and abacavir-based antiretroviral therapy (ART) in low-body weight treatment-naïve patients with HIV infection.DesignWe conducted a single-center retrospective cohort study of 503 Japanese patients who commenced on either tenofovir- or abacavir-based initial ART.MethodsThe incidence of renal dysfunction, defined as more than 25% fall in estimated glomerular filtration rate (eGFR) from the baseline, was determined in each group. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
46
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 35 publications
8
46
0
1
Order By: Relevance
“…Nishijima et al studied the effects of ABC and TDF on renal dysfunction in Japanese patient with HIV infections (5). These investigators reported that renal function declined more in TDF-based ART than in ABC-based ART in low-body weight, treatment-naä ƒve patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishijima et al studied the effects of ABC and TDF on renal dysfunction in Japanese patient with HIV infections (5). These investigators reported that renal function declined more in TDF-based ART than in ABC-based ART in low-body weight, treatment-naä ƒve patients with HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Japanese guideline, ABC/3TC and TDF/FTC are the primary recommended regimens for treatment-naä ƒve patients with HIV infections (4). However, renal function declines more in tenofovir-than in abacavir-based antiretroviral therapy in treatment-naä ƒve Japanese patients with HIV infection and having low body weight (5).…”
Section: Introductionmentioning
confidence: 99%
“…Although impairment of renal function was greater in patients under the tenofovir regimen (22.1%), impairment of renal function was also observed in patients under the abacavir regimen (13.5%). 30 In the AIDS Clinical Trials Group Study 5202 (ACTG), the frequency of Fanconi syndrome, toxic nephropathy, proteinuria, and renal failure was similar between patients treated with tenofovir/emtricitabine and those treated with abacavir/ lamivudine. 31 These findings confirm that although abacavir has a lower nephrotoxicity profile, it is still a nephrotoxic antiretroviral drug.…”
mentioning
confidence: 99%
“…The efficacy and safety of these two fixed-dose regimens in patients with different genetic backgrounds and body statures might not be similar to the results of previous trials, especially considering that the prevalence of HLA-B*5701 is zero in the Japanese population (7). Moreover, the degree of decrement in the renal function with TDF is larger in patients with a low body weight, such as the Japanese, which might limit the use of TDF in patients with a high risk for renal dysfunction (18)(19)(20). Based on the above described background, the present randomized trial was originally designed in 2007 to elucidate whether the viral efficacy of ABC/3TC is not inferior to that of TDF/FTC with ritonavir-(100 mg) boosted atazanavir (300 mg) in treatment-naïve Japanese patients, whose body weight is much lower than Whites or Blacks (21).…”
Section: Introductionmentioning
confidence: 74%
“…TDF-induced nephrotoxicity is of particular interest in this study because a low body weight is an important risk factor, and body stature was much smaller in this study population (median baseline body weight 64 kg), than in the ASSERT study (72 kg), which compared the renal function between patients receiving ABC/3TC and TDF/FTC with efavirenz in Europe (17,18,20). This study showed that changes in the renal function from baseline were not significantly different between the two arms, similar to the findings of the ASSERT study.…”
Section: Discussionmentioning
confidence: 99%